Nonribosomal Peptide Synthesis—Principles and Prospects. Issue 14 (21st March 2017) - Süssmuth, Roderich D.; Mainz, Andi
Abstract: Nonribosomal peptide synthetases (NRPSs) are large multienzyme machineries that assemble numerous peptides with large structural and functional diversity. These peptides include more than 20 marketed drugs, such as antibacterials (penicillin, vancomycin), antitumor compounds (bleomycin), and immunosuppressants (cyclosporine). Over the past few decades biochemical and structural biology studies have gained mechanistic insights into the highly complex assembly line of nonribosomal peptides. This Review provides state‐of‐the‐art knowledge on the underlying mechanisms of NRPSs and the variety of their products along with detailed analysis of the challenges for future reprogrammed biosynthesis. Such a reprogramming of NRPSs would immediately spur chances to generate analogues of existing drugs or new compound libraries of otherwise nearly inaccessible compound structures. Abstract : Size does not matter : Nonribosomal peptides (NRPs) are assembled by large multienzyme machineries and represent a structurally highly diverse class of natural products with various bioactivities. This Review provides a thorough overview of NRPs, including their bioactivities, biosynthesis pathways, and their structural variation through biocombinatorial approaches.